Modulation of cardiac resident macrophages immunometabolism upon high-fat-diet feeding in mice - Zhu, Simeng; Liu, Yujia; Xia, Guofang; Wang, Xiaoqing; Du, Ailian; Wu, Jin; Wang, Yanpeng; Wang, Yuanlong; Shen, Chengxing; Wei, Peng; Xu, Congfeng (Frontiers in Immunology, 2024)
Background: High-fat diet (HFD) contributes to various metabolic disorders and obesity, which are major contributors to cardiovascular disease. As an essential regulator for heart homeostasis, cardiac resident macrophages, may go awry and contribute to cardiac pathophysiology, upon HFD. Thus, to better understand how HFD induced cardiac dysfunction, this study intends to explore the transcriptional and functional changes in cardiac resident macrophages of HFD mice.Methods: 6-week-old C57/B6J female mice were fed with HFD or normal chow diet (NCD) for 16 weeks. After evaluation of cardiac functions by echocardiography, mouse hearts were harvested and cardiac resident CCR2 -macrophages were sorted, following by Smart sequencing. Bioinformatics analysis including GO, KEGG and GSEA analysis were employed to elucidate transcriptional and functional changes.Results: Hyperlipidemia and obesity were observed easily upon HFD. The mouse hearts also displayed more severe fibrosis and diastolic dysfunction in HFD mice.Smart sequencing and functional analysis revealed metabolic dysfunctions, especially lipid-related genes and pathways. Besides, antigen presentation related gene such as Ctsf, and inflammation, particularly for NF-κB signaling and complement cascades, underwent drastic changes in cardiac resident macrophages. GO cellular compartment analysis was also performed and showed specific organelle enrichment trends of involved genes.Dysregulated metabolism intertwines with inflammation in cardiac resident macrophages upon HFD feeding in mice, and further research on cross talk among organelles could shed more light on potential mechanisms.